No role for human papillomavirus in esophageal squamous cell carcinoma in China - Koshiol, Jill; Wei, Wen-Qiang; Kreimer, Aimee R.; Chen, Wen; Gravitt, Patti; Ren, Jian-Song; Abnet, Christian C.; Wang, Jian-Bing; Kamangar, Farin; Lin, Dong-Mei; Knebel Doeberitz, Magnus von; Zhang, Yu; et al. (International journal of cancer, 2010)
Certain regions of China have high rates of esophageal squamous cell carcinoma (ESCC). Previous studies of human papillomavirus (HPV), a proposed causal factor, have produced highly variable results. We attempted to evaluate HPV and ESCC more definitively using extreme care to prevent DNA contamination.
Gesehen am 22.03.2023